SHOKU BUNKA: WARNA BUDAYA DAN TRADISI DALAM MAKANAN JEPANG - Lina Rosliana (Universitas Diponegoro, 2017)
Japan has natural resources that can provide sufficient food, both from the mountains, the sea, and rivers. The four seasons it has also contributed to the diversity of natural products, which provide a variety of colors in the food. The seriousness of producing quality food, the use of unique food processing techniques, to artistic presentation, makes Japanese food a strong identity among traditional foods from other countries in the world. In its development, Japanese food openly receives influence from abroad, but still maintains its traditions, to create the concept of assimilation in it. Japan is able to pour cultural colors on its food and make Japanese food as a soft diplomacy of the country that is easily accepted by the international world. There are many factors that can be explored by researching Japanese food, so research on Japanese food can touch some of the domains, such as geography, health, sociology, and culture. This study will explore Japanese food from the eyes of culture. <a href=